Screening for a raised rectal temperature in Africa. Issue 4 (October 1993) - Jones, R J; O'Dempsey, T J; Greenwood, B M
Abstract : The main purpose of this study was to compare rectal and axillary temperature measurements in African children. Altogether 573 sick children were seen in an outpatient setting in rural West Africa. Rectal and axillary temperatures were measured and the parent or guardian was asked if they thought that the child had a raised body temperature. Normal ranges were defined from an age matched population of 203 healthy children. A raised axillary temperature predicted a raised rectal temperature with a sensitivity of 98% and a specificity of 88%. The parents' impression that their child had a fever was a less sensitive (89%) and less specific (59%) indicator of raised rectal temperature. A raised axillary temperature is a good screening test for a raised rectal temperature in African children.